Optogenetic manipulation of astrocytes from synapses to neuronal networks: A potential therapeutic strategy for neurodegenerative diseases. Issue 2 (10th August 2019) - Xie, Zhen; Yang, Qinghu; Song, Da; Quan, Zhenzhen; Qing, Hong
Abstract: Astrocytes are the most widespread and heterogeneous glial cells in the central nervous system and key regulators for brain development. They are capable of receiving neurotransmitters produced by synaptic activities and regulating synaptic functions by releasing gliotransmitters as part of the tripartite synapse. In addition to communicating with neurons at synaptic levels, astrocytes can integrate into inhibitory neural networks to interact with neurons in neuronal circuits. Astrocytes are closely related to the pathogenesis and pathological processes of neurodegenerative diseases (NDs). Recently, optogenetics has now been applied to reveal the function of astrocytes in physiology and pathology. Herein, we discuss the possibility whether optogenetics could be used to control the release of gliotransmitters and regulate astrocytic membrane channels. Thus, the capability of modulating the bidirectional interactions between astrocytes and neurons in both synaptic and neuronal networks via optogenetics is evaluated. Furthermore, we discuss that manipulating astrocytes via optogenetics might be an effective way to investigate the potential therapeutic strategy for NDs. Main points: The abnormal crosstalk between astrocytes and neurons is related to the onset of neurodegenerative diseases (NDs). Optogenetic manipulation of astrocytes may be an effective approach to explore the pathology and therapeutic targets of NDs.